2012
DOI: 10.1039/c2sm25536g
|View full text |Cite
|
Sign up to set email alerts
|

Novel gelatin–PHEMA porous scaffolds for tissue engineering applications

Abstract: In the present work, novel bicomponent polymeric hydrogels based on methacrylamide-modified gelatin (MAG) and 2-hydroxyethyl methacrylate (HEMA) have been prepared by cross-linking polymerization using photoinitiation. Five types of novel hydrogels have been prepared using different MAG/HEMA ratios between 1/0.5 and 1/10 w/w. Subsequently, porous scaffolds were obtained via a cryogenic treatment followed by freeze-drying. Physico-chemical measurements as well as in vitro degradation tests have been performed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 37 publications
1
61
0
Order By: Relevance
“…Fig. 13,23 The blood clotting behaviors of the hydrogels are shown in Fig. As expected, the introduction of gelatin improves the wettability and hydrophilicity of the NC gel surfaces, which in turn increase the antithrombogenicity.…”
Section: In Vitro Blood Compatibilitymentioning
confidence: 68%
See 1 more Smart Citation
“…Fig. 13,23 The blood clotting behaviors of the hydrogels are shown in Fig. As expected, the introduction of gelatin improves the wettability and hydrophilicity of the NC gel surfaces, which in turn increase the antithrombogenicity.…”
Section: In Vitro Blood Compatibilitymentioning
confidence: 68%
“…20 As a gelatin derivative, MA-gelatin retains the biocompatibility of gelatin without impairing its hydrophilicity; thus, the presence of MA-gelatin can signicantly improve the adhesion, multiplication and migration of cells on hydrogels, favourable for the fabrication of tissue engineering materials. 23 Therefore, it can be expected that the combined processes of polymerization and crosslinking were simultaneously performed during the synthesis of MA-gelatin crosslinked hydrogels. 23 Therefore, it can be expected that the combined processes of polymerization and crosslinking were simultaneously performed during the synthesis of MA-gelatin crosslinked hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…A wide use of HEMA gels in biomedical applications is explained by the facts that these hydrogels are non-toxic, inert, and biocompatible , whereas their mechanical and physical properties are close to those of extracellular matrix (ECM). Shortcomings of a neat HEMA gel which does not allow cell adhesion and proliferation can be overcome by copolymerization of HEMA with other monomers (Holt et al, 2011;Kemal et al, 2011;Dragusin et al, 2012;John et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…7,48 For instance, methacrylamide-modified gelatin-2-hydroxyethyl methacrylate porous scaffolds have been fabricated using the freeze-drying method. 49 Human foreskin fibroblasts seeded onto these novel scaffolds still maintain high (95%) viability after 7 days in culture in vitro. Autissier et al 48 prepared a porous polysaccharide-based scaffold using the freeze-drying method, and demonstrated that pore diameter (55-243 µm) and porosity (33%-68%) in the scaffolds can be regulated by the freeze-drying pressure ( Figure 3C and D).…”
Section: Freeze-dryingmentioning
confidence: 99%